2014
DOI: 10.1890/13-1996.1
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational phenotypic plasticity links breeding phenology with offspring life‐history

Abstract: The timing of seasonal life-history events is assumed to evolve to synchronize life cycles with the availability of resources. Temporal variation in breeding time can have severe fitness consequences for the offspring, but the interplay between adult reproductive decisions and offspring phenotypes remains poorly understood. Transgenerational plasticity (TGP) is a potential mechanism allowing rapid responses to environmental change. Here, we investigated if experimentally delayed breeding induces TGP in larval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
45
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 47 publications
(74 reference statements)
13
45
1
Order By: Relevance
“…In our study, tadpoles increased their development rates in response to delayed hatching (i.e. shortened their larval period), which agrees with previous studies on the species (Orizaola et al , Richter‐Boix et al ). This is also in accordance with studies conducted in other organisms living in temperate environments that shorten their development period after the exposure to a simulated increase in time‐constraints (De Block and Stoks , Strobbe and Stoks , Stoks et al ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, tadpoles increased their development rates in response to delayed hatching (i.e. shortened their larval period), which agrees with previous studies on the species (Orizaola et al , Richter‐Boix et al ). This is also in accordance with studies conducted in other organisms living in temperate environments that shorten their development period after the exposure to a simulated increase in time‐constraints (De Block and Stoks , Strobbe and Stoks , Stoks et al ).…”
Section: Discussionsupporting
confidence: 93%
“…Embryos in the non‐delayed hatching treatment were maintained in a 19°C room until hatching; whereas embryos in the delayed hatching treatment were transferred to a 4°C climate room for 12 days two days after fertilization and moved back to constant 19°C after these 12 days. The exposure to low temperature arrests embryonic development almost completely, and induces compensatory growth during the larval stage (Orizaola et al , , Richter‐Boix et al ).…”
Section: Methodsmentioning
confidence: 99%
“…We filled the experimental buckets with reconstituted soft water (see Richter‐Boix et al, , for details) and renewed the water twice a week. We fed larvae ad libitum with par‐boiled chopped spinach every second day.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, we demonstrated transgenerationally induced compensatory responses to changes in breeding phenology in amphibians (Richter‐Boix et al. ). After an experimental delay in breeding, tadpoles accelerated growth and development, even in the absence of environmental cues (Richter‐Boix et al.…”
Section: Introductionmentioning
confidence: 91%
“…, Richter‐Boix et al. ). While understanding the impact of changes in phenology on the responses to other environmental stressors, such as predation risk, is crucial for evaluating the potential of organisms to successfully respond to the current rate of environmental change experienced in nature, only a few papers have examined the interactive effects between phenology and predation risk in vertebrates with complex life cycles (see, e.g., Altwegg , Urban , Orizaola et al.…”
Section: Introductionmentioning
confidence: 99%